Plumbum removal by using chitosan as absorbent / Noorluqman Hakim Salleh Rashid ... [et al.] - Salleh Rashid, Noorluqman Hakim; Mohd Fouzi, Nursyaza Najwa; Hassan, Mohamad Hasni; Jafprinin, Nur Afiqah; Sanusi, Salmi Nur Ain; Rozali Annuar, Nur Hazirah (2018)
The study focuses on the potential of chitosan as a natural biopolymer adsorbent for plumbum removal from the simulated waste water by using jar test. When using Chitosan powder the absorption process had occur. The analysis that had been conducted in this experiment were the percentage removal of plumbum by using Inductively Coupled Plasma (ICP) and pH test. The efficiency of Chitosan as natural absorbent was to be determined based on the two parameters conducted, which were the effect of amount of absorbent and the mixing speed of the jart test. In this research, 5 samples of simulated waste water containing lead (II) nitrate were tested under fixed retention time which was 30 minutes for every parameter. This study showed that 2g of Chitosan could effectively remove 98.65% of plumbum, at the maximum of200 rpm of the mixing speed. This research also showed that Chitosan gave better removal performance compared to chemical absorbent such as aluminium sulphate